A new model to investigate the impact of innovative IT services on smart urban growth: The mediating role of urban planners' knowledge. (26th February 2021) - Liu, Dapeng; Zhao, Mao; Xu, Haiqing; Mehrgan, Mansoureh
Abstract: Cities have turned into intelligent urban zones via new data services like the semantic Web, cloud computing, mobile gadgets, and the Internet of Things (IoT). We can organize smart city policies by numerous technological and policy interferences to improve the efficacy, efficiency, and flexibility of urban infrastructures. Scholars have greatly focused on the development of smart cities. In this study, the influence of Information Technology (IT) services on smart urban growth to make a model for urban decision makers was examined. Data were collected from 201 managers and urban planners. The questionnaires using SPSS 25 and SMART‐PLS 3.2 were statistically analyzed. The outcomes show that cloud services had positive effects on urban planners' knowledge. In addition, the influence of Near Field Communication (NFC) services on urban planners' knowledge is positive and significant. The findings have also shown that IoT services are important factors in urban planners' knowledge. Another point was that urban planners' knowledge has significantly affected reliability, sustainability, social improvement, energy efficiency, and environmental improvement. At the managerial level, the findings provided recommendations to urban managers and planners.